Growth and antioxidant system of Chinese kale microgreens in response to different illumination of light sources - Tantharapornrerk, Naruchon; Vichitsoonthonkul, Taweerat; Techavuthiporn, Chairat; Photchanachai, Songsin (My University, 2023)
Light-emitting diodes (LEDs) are commercially used as a light source to improve plant growth and antioxidants accumulation. Growth and antioxidant system in Chinese kale microgreens illuminated with blue, red and white LEDs and sunlight, as a control, with the same duration of illumination were investigated. The red LED with low light intensity significantly enhanced hypocotyl length and fresh weight of microgreens, while blue and white LEDs and sunlight showed fairly comparable effects. The synergistic effect of blue, green and red LEDs, as white LED was the most effective in enhancing the accumulation of secondary metabolites, namely, total glucosinolates, phenolic compounds and total ascorbic acid. Microgreens grown with blue and white LEDs showed higher DPPH (1,1-diphenyl-1-picrylhydrazyl) radical scavenging activity and ferric reducing antioxidant power, whereas ABTS [2,2’-Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)] radical cation (ABTS) fared better under sunlight and blue LEDs. Overall, microgreens treated with red LED significantly reduced H2O2 and lipid peroxidation by only secondary metabolites. While blue and white LEDs treated samples utilised secondary metabolites, as well as, catalase and ascorbate peroxidase when compared to less effective superoxide dismutase in the control samples. The results suggest that light wavelength was a majority factor in enhancement antioxidant accumulation.
Keywords: Antioxidant system; Chinese kale microgreens; enzymatic antioxidants; light-emitting diodes (LEDs); non-enzymatic antioxidants; secondary metabolites